Improving Children's Knowledge About When Teeth Erupt with The Use of Flashcards - Nendika Dyah Ayu Murika` Sari; Sandy Christiono; Shania Rahma Fitriani; Ikhwan Tri Julian (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Persistence is often found in children with mixed dentition. The level of knowledge of parents and children about the timing of tooth eruption can be one of the causes of the high prevalence of tooth persistence in children. Knowledge of tooth eruption timing is important for children to have. Flashcard media can be used to help children learn more.The purpose of this activity is to increase children's knowledge about tooth eruption time through flashcard media. The method used is an interactive playing method with flashcards. The interactive play method with flashcards involves all students by dividing the children into groups, each group having a maximum of 10 children. Each group received one flashcard package with an accompanying educator. One flashcard package consists of 20 cards containing educational material about teeth and their functions, the number of teeth, and the time of tooth eruption. To find out the increase in knowledge, a pretest and posttest were carried out. The result of this activity was that there was an increase in children's knowledge, and the results of the paired T-test showed a significant difference (p<0.05). Conclusion: Flashcard media is effective for increasing children's knowledge about the timing of tooth eruption.